Comparative Assessment of Goods and Services Provided by Grazing Regulation and Reforestation in Degraded Mediterranean Rangelands. (19th March 2015) - Papanastasis, Vasilios P.; Bautista, Susana; Chouvardas, Dimitrios; Mantzanas, Konstantinos; Papadimitriou, Maria; Mayor, Angeles G.; Koukioumi, Polina; Papaioannou, Athanasios; Vallejo, Ramon V.
Abstract: Several management actions are applied to restore ecosystem services in degraded Mediterranean rangelands, which range from adjusting the grazing pressure to the removal of grazers and pine plantations. Four such actions were assessed in Quercus coccifera L. shrublands in northern Greece: (i) moderate grazing by goats and sheep; (ii) no grazing; (iii) no grazing plus pine ( Pinus pinaster Aiton) plantation in forest gaps (gap reforestation); and (iv) no grazing plus full reforestation of shrubland areas, also with P . pinaster . In addition, heavy grazing was also assessed to serve as a control action. We comparatively assessed the impact of these actions on key provisioning, regulating and supporting ecosystem services by using ground‐based indicators. Depending on the ecosystem service considered, the management actions were ranked differently. However, the overall provision of services was particularly favoured under moderate and no grazing management options, with moderate grazing outranking any other action in provisioning services and the no grazing action presenting the most balanced provision of services. Pine reforestations largely contributed to water and soil conservation and C sequestration but had a negative impact on plant diversity when implemented at the expense of removing natural vegetation in the area. Heavy grazing had the lowest provision of ecosystem services. It is concluded that degraded rangelands can be restored by moderating the grazing pressure rather than completely banning livestock grazing or converting them into pine plantations. Copyright © 2015 John Wiley & Sons, Ltd.